Pengamanan Ruangan Dengan Dfrduino Uno R3, Sensor Mc-38, Pir, Notifikasi Sms, Twitter - Siswanto Siswanto; Gunawan Pria Utama; Windu Gata (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Security officers can not monitor the security of the financial space at all times especially outside working hours or evenings because the financial room is on the 3rd floor. Security guards are not warned quickly if there are people who do not have the right to enter the financial room at the time of blank or after hours. The purpose of this research is to design an application that can monitor the security of financial space by giving information or giving warning in the form of alarm and sending SMS and Twitter notification to security officer if there are people who do not have access rights of financial space, using DFRduino Uno R3 microcontroller, MC-38 magnets, PIR sensors, Alarms, Sony Ericsson Z530i phone, wifi modem, and Bluetooth. If a door or movement is detected the computer will send a command to DFRduino which is then forwarded to the alarm to give a sound alert. And with the Hanphone Sony Ericsson Z530i with a connection via Bluetooth Mobile can connect with the application so that the computer can send notification SMS alert to the number that has been registered as the recipient of SMS and notification via Twitter to the username that has been registered. With the magnet sensor it is possible to detect if the door or window is forced and PIR sensor is used as a support if the magnetic sensor is not working or if the thief enter the room not through the door or window. PIR Sensor installed in the room allows all activities that occur will be able to monitor well. If there is a security breach or infiltration it will be quickly known because there are warnings via SMS and Twitter that can provide information to security personnel to perform actions quickly so that cases can be resolved thoroughly.